The Struggle over Nature and Relaxation in (Sub)Urban Space: The Case of Garden Colonies in Kbely, Prague 19 - Pauknerová, Karolína; Gibas, Petr (Lidé města, 2011)
The article deals with a change of an urban space in Prague-Kbely as it was reflected in the municipal press, with special attention to the fate of allotment garden colonies. There used to be several garden colonies in the suburban Prague district of Kbely. In recent years some of them had to disappear in order to make space for new development of Kbely. We propose an analysis of how this change was reflected in the local municipal paper “Kbelák,” which is funded by the municipality and is distributed free to every household in the district.